Apple phlorizin reduce plasma cholesterol by down-regulating hepatic HMG-CoA reductase and enhancing the excretion of fecal sterols. (November 2019) - Wang, Hao; Sun, Zhen-ou; ur-Rehman, Rizwan; Riaz, Sania; Shen, Ting-Ting; Fan, Zhen-Chuan; Liu, Dong
Graphical abstract: Highlights: Phlorizin decreased plasma CETP and HMG-CoA-R activity and TG, TC levels. Phlorizin down-regulated intestinal NPC1L1, HMG-CoA-R mRNA levels. Phlorizin decreased liver cholesterol and increased fecal acidic and neutral sterol. Molecular docking hinted that phlorizin was a HMG-CoA-R inhibitor. Abstract: This study was aimed to examine the effect of apple phlorizin on lipid accumulation in HepG2 cell and hamsters (Thirty-six male Golden Syrian hamsters) fed with atherogenic diet. Dietary supplementation of 0.9% phlorizin significantly decreased the level of plasma total cholesterol (TC), triacylglycerols (TG), activity of cholesteryl ester transfer protein (CETP) and liver 3-hydroxy-3-methyl glutaryl coenzyme A reductase (HMG-CoA-R), alongside down-regulated the gene expressions of intestinal Niemann-Pick C1-like 1 (NPC1L1), HMG-CoA-R and up-regulated ATP-binding cassette transporters subfamily G members 5/8 (ABCG5/8) gene. Phlorizin increased the excretion of sterols, reduce absorption of dietary cholesterol and de novo synthesis of cholesterol. Furthermore, in silico studies revealed the binding profile of the phlorizin and HMG-CoA-R, hinted at the molecular interactions that are responsible for its activity. These results suggested that dietary supplementation of phlorizin could potentially possess cholesterol-lowering activity by increasing the excretion of sterols and mediating the endogenous cholesterol metabolic management.